High-level nitrogen removal achieved by Feammox-based autotrophic nitrogen conversion - Xiaohui Cheng; Lanlan Hu; Tao Liu; Xiang Cheng; Jiyun Li; Kangning Xu; Min Zheng (Water Research X)
Anaerobic ammonium oxidation coupled with Fe(III) reduction (Feammox) is an essential process in the geochemical iron and nitrogen cycling. This study explores Feammox-based nitrogen removal in a continuous laboratory up-flow bioreactor stimulated by intermittently adding 5 mM Fe(OH)3 at intervals of approximately two months. The feed was synthetic wastewater with a relatively low ammonium concentration (∼100 mg N/L), yet without organic carbon in order to test its autotrophic nitrogen removal performance. The operation of this system showed the achievement of high-level ammonium and total nitrogen removal efficiency (∼97% and ∼90% on average, respectively) within four months of operation, along with a relatively practical rate of ∼50 mg N/(L·d). The demand of Fe(Ⅲ) for ammonium removal during the whole bioreactor operation was estimated to be only 0.033, two orders of magnitude less than that calculated based on the Feammox reaction producing nitrogen gas. A series of assays on Fe(II) oxidation with different oxidants (O2, NO2− and NO3−) in abiotic and biotic batch tests further revealed an important role of Fe(II) oxidation processes, likely driven by microbial nitrate reduction and chemical oxygen reduction, in assisting the regeneration of Fe(III) for continuous Feammox-based nitrogen removal. This work demonstrates that Feammox-based autotrophic nitrogen conversion is a potential option for future wastewater treatment.